Processos de criação em performance e as práticas comunicativas - Gorzillo, Maria Regina (2019)
This research investigates the artistical contemporary process of creation from specific projects of Lygia Pape, Eleonora Fabião, Lhola Amira and the collective Opavivará!. On these processes, there are actions that call spectators to be part of the creation construction through different ways of being in contact with these works of art. In this sense, the hypothesis is that when studying the process of creation as a network construction, it is possible to contextualize the bodyenvironment relation. Besides that, looking at the performances from the theory of the researcher Diana Taylor, which points to the multiple elements of exchange in these processes. Moreover, it is also evidenced the relation with the communicational and cultural aspects in the direction of expanding the debates about the artistic proposes that make the reception to experience the work of art at different forms. The theoretical discussions are guided by arguments based on the elements of the network interaction, whose prominence is given to the bodyspace relation, observing the extension of the gallery to the street and some reflections about the spectator. The objective is to use artists’ procedures, based on the available documents, as a mean to the process of criticism and to problematize aspects and marks of communication and semiosis involving artists and spectators in the cultural environment. The research methodology is structured from the studies of Cecilia Almeida Salles and from the perspective of creation network as well as process criticism. Among other authors, who are part of the dialogues about the processes, are: Amálio Pinheiro, Diana Taylor, Edgar Morin, Eleonora Fabião, Flávio Desgranges, Manuel Delgado, Paul Zumthor and Richard Schechner